The use of pulsed electric acoustic technique for measuring electric field profiles in ferroelectric ceramic - Giacometti, J. A. [UNESP]; Eiras, J. A.; Lente, M.; Tomioka, J.; Wisniewski, C.; Moura, W. A. (Institute of Electrical and Electronics Engineers (IEEE), 2002)
The pulsed electric acoustic technique, PEA, have been usually applied to probe space charge profiles in polymers. In this work we show preliminary results obtained with lead zirconate-titanate and niobium, PZTN, ferroelectric ceramic samples. Experiments showed that induced charge densities on sample electrodes are mainly due to the ferroelectric polarization of the sample. We present results of the typical PEA response and the procedure to deconvolute the signal in order to obtain the charge densities and the electric field profiles. The PEA setup allows us to show a non-uniform polarization during ferroelectric switching.
Keywords: Acoustic wave propagation; Convolution; Electric field measurement; Electric space charge; Electrodes; Ferroelectric ceramics; Ferroelectricity; Lead compounds; Niobium; Polarization; Polymers; Charge density; Ferroelectric polarization; Ferroelectric switching; Lead zirconate-titanate; Non-uniform polarization; Pulsed electric acoustic technique; Acoustoelectric effects